Research-based insights on initial teacher education in Spain - Sancho-Gil, Juana M.; Sánchez-Valero, Joan-Anton; Domingo-Coscollola, Maria (European Journal of Teacher Education, 2017)
This paper builds on two research projects on initial and in-service education of teachers, their professional experience, and the pathways they travelled to become teachers. The policy documents analysed and the teachers’ professional histories, the micro-ethnographies and the discussion groups developed, allowed us to draw a broad picture of the development of the initial teacher education in Spain. Three fundamental stages were identified: (a) developmentalism and the last stage of Franco’s dictatorship; (b) constructing democracy and (c) the implementation of the European Higher Education Area. Our research shows that the reform implemented in each period represented a clear intention to professionalise teachers’ work and to move beyond the view of initial education as vocational training by transferring it to the university. Meant a move towards improving the relationship between theory, educational research and practice; and left a set of unfulfilled challenges.